Pedagogical scaffolding in L2 teaching: An examination of an EFL summary writing lesson - Xiaomei Sun (ELT Forum: Journal of English Language Teaching, 2024)
Underpinned by sociocultural theory, scaffolding is a long-standing term but remains an under-researched topic in L2 pedagogy studies. With the aim of investigating what pedagogical scaffolding an EFL teacher applied to a genre-based approach to L2 writing and the effect of the scaffolding, this study scrutinised a lesson plan as part of a school-based workbook and students’ response to the scaffolding reflected in their written works. Data were collected from teaching materials, students’ written works (N=42), and a semi-structured interview with the teacher participant. Results indicate that multi-layered and multi-dimensional scaffolding was manifested in the design and implementation of the writing lesson. Analysis of the story summaries reveals that the teacher’s scaffolding and guidance resulted in students’ general application of genre-specific features and focused grammatical structures in their writing. Meanwhile, different degrees of conformity and creativity were demonstrated in the written works: less competent L2 learners displayed greater conformity to the teacher’s instructions, while students of higher L2 proficiency displayed more creativity in their works. This study provides suggestions for adopting multi-layered and multi-dimensional scaffolding in EFL writing lessons.